Factors influencing students' peer feedback uptake: instructional design matters. Issue 8 (16th November 2020) - Mercader, Cristina; Ion, Georgeta; Díaz-Vicario, Anna
Abstract: Peer feedback is a strategy that allows students to be involved in the assessment process, making them more conscious about the teaching and learning activities. However, different instructional designs can influence learning in different ways. Our paper aims to identify whether peer feedback instructional designs influence students' learning perceptions. We performed a comparative study at a Faculty of Education, tracking students during their first two years of a teacher education program. Students participated in two consecutive peer feedback experiences using different instructional designs. Results show that students perceive that long-term interventions with prior training and double-loop feedback processes are more useful for their performance than a short-term experience without face-to-face training and single-loop feedback processes. They perceive more benefits when they provide feedback than when they receive it. Lecturers should take these variables into account when designing peer feedback activities in order to maximise the impact on students' learning.